2020
DOI: 10.3390/biomedicines8080254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Electronegative Low-Density Lipoprotein Cholesterol in Atherothrombosis

Abstract: Despite the numerous risk factors for atherosclerotic cardiovascular diseases (ASCVD), cumulative evidence shows that electronegative low-density lipoprotein (L5 LDL) cholesterol is a promising biomarker. Its toxicity may contribute to atherothrombotic events. Notably, plasma L5 LDL levels positively correlate with the increasing severity of cardiovascular diseases. In contrast, traditional markers such as LDL-cholesterol and triglyceride are the therapeutic goals in secondary prevention for ASCVD, but that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…The exact toxic components of cigarette smoke and the mechanisms involved in CS-related cardiovascular dysfunction are largely unknown, because it is also observed that non-smoker without family history develop MI even in the early ages of the life span. but CS increases inflammation, thrombosis, and oxidation of lowdensity lipoprotein cholesterol (Chu et al, 2020). Recent experimental and clinical data support the hypothesis that cigarette smoke exposure increases oxidative stress as a potential mechanism for initiating cardiovascular dysfunction.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…The exact toxic components of cigarette smoke and the mechanisms involved in CS-related cardiovascular dysfunction are largely unknown, because it is also observed that non-smoker without family history develop MI even in the early ages of the life span. but CS increases inflammation, thrombosis, and oxidation of lowdensity lipoprotein cholesterol (Chu et al, 2020). Recent experimental and clinical data support the hypothesis that cigarette smoke exposure increases oxidative stress as a potential mechanism for initiating cardiovascular dysfunction.…”
Section: Methodsmentioning
confidence: 77%
“…Smoking proved to be the significant risk factor for both genders and remained the major health hazard leading to MI. Cigarette smoking ( CS) impacts all phases of atherosclerosis from endothelial dysfunction to acute clinical events, the latter being largely thrombotic (d'Alessandro et al, 2020;Head et al, 2017). The exact toxic components of cigarette smoke and the mechanisms involved in CS-related cardiovascular dysfunction are largely unknown, because it is also observed that non-smoker without family history develop MI even in the early ages of the life span.…”
Section: Methodsmentioning
confidence: 99%
“…Electronegative LDL (LDL(−)) is a modified fraction of the LDL that holds physical and chemical characteristics that differ from those of native LDL, such as increased lipoprotein-associated phospholipase A2 activity (Lp-PLA2), ceramide, clusterine, nonesterified fatty acid content, as well as increased aggregation level [117]. LDL(−) normally comprises around 3−5% of the total LDL plasma quantity, yet in certain CV pathologies this fraction rises [118]. A moderate rise of LDL(−) is commonly observed in patients with classical CV risk factors such as hypercholesterolemia, active smoking, diabetes, and metabolic syndrome [119][120][121][122].…”
Section: Lipid-based Biomarkersmentioning
confidence: 99%
“…The therapeutic goal of controlling L5 should be to lower its plasma concentration below 1.7 mg/dL. If the L5 concentration is higher than 1.7 mg/dL, a lipid-lowering treatment, such as statins or PCSK9 inhibitors, may be required regardless of the absolute LDL level [ 130 ].…”
Section: Proposed Therapeutic Strategies For Targeting Ascvd In Patients With Airdsmentioning
confidence: 99%